FITOREMEDIASI AIR LIMBAH PENCELUPAN BATIK PARAKANNYASAG, TASIKMALAYA MENGGUNAKAN KI APU (Pistia stratiotes L.) - Tri Cahyanto; Tony Sudjarwo; Shinta Putri Larasati; Afriansyah Fadillah (Scripta Biologica, 2018)
Batik home industry discharge untreated wastewater that can cause pollution to sewage water and its environment. Phytoremediation is the utilization of plants for environmental clean-up or reduces harmful contaminants including heavy metals such as chrome (Cr) of batik dyes. Water cabbage (Pistia stratiotes L.) locally named as Ki Apu is an aquatic plant known for its ability to reduce the Cr level in wastewater. This study aimed to determine the efficiency Ki Apu to reduce Cr level from batik dyeing wastewater from Parakannyasag, Tasikmalaya. This study was an experimental using Ki Apu from Indihiyang paddy field of Tasikmalaya. 12 individual of Ki Apu were grown on a 20 L water tank with different batik dyeing wastewater concentration of 0%, 25%, 50%, 75%, and 100%, each with five replicates. After 14 days the results showed the highest Cr reduction was measured at 77.5% occurred in 100% wastewater tank. Ki Apu leaf changed its leaf chlorophyll content with the highest estimate of 0.4 mg/L for chlorophyll-b and 1.3 mg/ L for the total chlorophyll; both occurred in 75% wastewater tank. The highest rate of phytoremediation indicated by BOD measure was at 33.4 mg/L/day occurred in 100% wastewater tank and by turbidity measure was at 23.3 mg/L/day occurred in 75% wastewater tank. Ki Apu is considered having a high phytoremediation effectivity to reduce Cr content in batik dyeing wastewater in Parakannyasag, Tasikmalaya.